2005
DOI: 10.1191/1352458505ms1208oa
|View full text |Cite
|
Sign up to set email alerts
|

A comparative audit of anticardiolipin antibodies in oligoclonal band negative and positive multiple sclerosis

Abstract: It has been suggested that multiple sclerosis (MS) patients with positive anticardiolipin antibodies (ACLA) have some atypical features, including absent oligoclonal bands (OCB) in the cerebrospinal fluid (CSF). Our aim was to compare the frequencies of ACLA and related laboratory and clinical features in OCB negative (OCB-) and positive (OCB+) MS patients. We compared 41 OCB- patients attending a MS Clinic in a tertiary referral center, with 206 OCB+ patients. ACLA, anti-beta2-glycoprotein and other autoantib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
2
3
0
Order By: Relevance
“…[4], [8], [12], [14], [15] It is possible that potential inclusion of NMO/NMOSD patients may have influenced these results. Our data is in agreement with studies [3][4], [6][7], [9], [10], [13], [22], [24] that have identified no association with clinical severity. Of note, two recent studies have suggested that MRI measurements of disease burden, including T2 lesion volume, may be associated with the presence of antiphospholipid autoantibodies in patients with MS. [5], [8] Further data is needed to confirm the significance of this finding.…”
Section: Discussionsupporting
confidence: 93%
“…[4], [8], [12], [14], [15] It is possible that potential inclusion of NMO/NMOSD patients may have influenced these results. Our data is in agreement with studies [3][4], [6][7], [9], [10], [13], [22], [24] that have identified no association with clinical severity. Of note, two recent studies have suggested that MRI measurements of disease burden, including T2 lesion volume, may be associated with the presence of antiphospholipid autoantibodies in patients with MS. [5], [8] Further data is needed to confirm the significance of this finding.…”
Section: Discussionsupporting
confidence: 93%
“…A different pathogenesis, involving aCL Ab, was suggested for these patients, but this study has been criticised because patients were preselected regarding their atypical clinical manifestations. A recent study showed that MS patients without OCB in their CSF showed aCL Ab positivity more frequently than OCB positive patients 13. This is in line with our study, in which of four aCL Ab positive MS patients out of five tested for OCB, bands were absent in CSF.…”
Section: Discussionsupporting
confidence: 92%
“…CNS APS and MS may be difficult to distinguish also from an immunological perspective, as the aPL antibody isotypes may involve IgG, IgM or IgA and therefore not always detected as the characteristic mirror pattern (positivity in serum and cerebrospinal fluid, CSF) or even of oligoclonal bands (OCB; predominant intrathecal antibody production; Cuadrado et al, 2000; Vilisaar et al, 2005). The two diseases resemble each other also for the epidemiological features of affected population, the relapsing-remitting course and for their appearance in neuroimaging (Figure 1).…”
Section: Current Challenges In the Diagnosis And Management Of The Anmentioning
confidence: 99%